Investigation of the application of Nd : YAG laser welding to couple photonic devices and packaging - Mohammad, Fadhali (2007)
In this paper we discuss some investigations and analyses of the various parameters, which contribute to increase the coupling efficiency of a laser diode to a single mode fiber-coupling using the lens coupling, which provides a coupling efficiency of about 75% at the optimum working distance. The separation between the coupling optics and the single mode fiber is in the range of 5-10 Î¼m. The alignment during the coupling process and welding of the lens holder, fiber ferrule, and welding clips was carried out using the automated laser welding system, LW4000S from Newport. The results of optimizing the laser beam parameters to produce sound welds with small heat affected zones (HAZ) when changes occur in the weld dimensions, as a result of a change in the laser beam parameters, are also discussed. The weld ability of various metals was checked to determine the suitability for the base material and welding tools for packaging of photonic devices. Â© 2007 Old City Publishing, Inc.